Intonation and gesture as bootstrapping devices in speaker uncertainty - Hübscher, Iris; Esteve-Gibert, Núria; Igualada, Alfonso; Prieto, Pilar (First language, 2017)
This study investigates 3- to 5-year-old children’s sensitivity to lexical, intonational and gestural information in the comprehension of speaker uncertainty. Most previous studies on children’s understanding of speaker certainty and uncertainty across languages have focused on the comprehension of lexical markers, and little is known about the potential facilitation effects of intonational and gestural features in this process. A total of 102 3- to 5-year-old Catalan-speaking children participated in a comprehension task which involved the detection of uncertainty in materials that combined lexical, intonational and gestural markers. In a between-subjects design, the children were either administered the lexical condition (where they were exposed to lexical and gestural cues to uncertainty) or the intonation condition (where they were exposed to intonational and gestural cues to uncertainty). Within each condition, three different presentation formats were used (audio-only, visual-only and audio-visual) in a within-subjects design. The results indicated that all the children performed better overall when they had gestural cues present. Furthermore, in comparison with the older group, the younger group was more sensitive to intonational marking of speaker uncertainty than to lexical marking. This evidence suggests that the intonational and gestural features of communicative interactions may act as bootstrapping mechanisms in early pragmatic development.